Analisis Penerapan Tax Control Framework dan Kewajiban Perpajakan atas Pajak Pertambahan Nilai pada PT Cublak Suweng - Moch. Yusril Ihza Mahendra; Ratna Anggraini Aripratiwi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The operational complexity of manufacturing companies has the potential to create gaps in tax non-compliance. Internal audits of tax aspects periodically and using a tax control framework-based approach can be carried out to ensure compliance with tax regulations and minimize tax risks. PT Cublak Suweng as a manufacturing company in Sidoarjo that has received the title of 100 Largest Taxpayers 2023. So this study aims to conduct a tax control framework analysis on tax obligations for VAT at PT Cublak Suweng. The method used is qualitative with a case study approach. The results obtained are that PT Cublak Suweng has fulfilled the components or framework of the tax control framework on tax obligations for VAT, and the framework can be carried out properly. However, further improvements are still needed to be more effective and optimal. This is because VAT reporting, in several Tax Periods, there are still frequent corrections.